Non-HDL Cholesterol is a More Superior Predictor of Small-Dense LDL Cholesterol than LDL Cholesterol in Japanese Subjects with TG Levels ＜400 mg/dL - Moriyama, Kengo; Takahashi, Eiko (Journal of Atherosclerosis and Thrombosis, 2016)
Aim: The Japan Atherosclerosis Society (JAS) guidelines for the diagnosis and treatment of hyperlipidemia in Japanese adults recommend using low-density lipoprotein cholesterol (LDL-C) calculated by Friedewald formula (F_LDL-C) for subjects with triglyceride (TG) levels ＜400 mg/dL and non-high-density lipoprotein cholesterol (non-HDL-C) levels for subjects with TG levels ≥400 mg/dL. Because small-dense LDL particles are more atherogenic than large LDL particles, we sought the better lipid parameter which was more reflective of the high small-dense LDL-C (sdLDL-C) levels in subjects with TG levels ＜400 mg/dL.Methods: This study included 769 Japanese subjects who met our inclusion criteria and underwent an annual health examination, including sdLDL-C analyses.Results: The correlation coefficient of non-HDL-C for sdLDL-C (r=0.760) was significantly higher than that of F_LDL-C (r=0.601). The area under the curve (95% confidence interval) was 0.771 (0.731, 0.811) for F_LDL-C and 0.871 (0.842, 0.901) for non HDL-C, which showed significantly higher predictive value for more than fourth quartile value of sdLDL-C (46 mg/dL). The optimal cut-off point of non-HDL-C was 158 mg/dL. Even in subjects stratified by waist circumstance, homeostasis model assessment of insulin resistance, TG, and F_LDL-C levels and non-HDL-C showed stronger relationships with sdLDL-C than F_LDL-C. Moreover, non-HDL-C showed a better relationship with sdLDL-C than total cholesterol (TC), TC/HDL-C, and non-HDL-C/HDL-C.Conclusion: Our data suggested that non-HDL-C is superior to F_LDL-C and one of the reliable surrogate lipid markers of sdLDL-C in Japanese subjects with TG levels ＜400 mg/dL.